2013
DOI: 10.1074/jbc.m113.499012
|View full text |Cite
|
Sign up to set email alerts
|

Control of DNA Replication by the Nucleus/Cytoplasm Ratio in Xenopus

Abstract: Background:The duration of S phase in Xenopus is controlled by the nucleus/cytoplasm ratio through unknown mechanisms. Results: Modulation of protein phosphatase 2A (PP2A) levels controls origin firing at high nucleus/cytoplasm. Conclusion: Depletion of PP2A and its B55␣ subunit at high nucleus/cytoplasm causes an extension of S phase. Significance: This mechanism may influence cell cycle remodeling that occurs in early embryogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…A second group also investigated the effect of the nucleus to cytoplasm ratio on the rate of DNA replication in Xenopus egg extracts (Murphy and Michael, 2013). By titrating sperm chromatin, they found that there is an increase in the time required to replicate sperm nuclei at high nucleus to cytoplasm ratios and, consistent with the work of Collart et al (2013), that this is caused by a decrease in replication origin activation.…”
Section: Mechanisms Regulating Changes To the Cell Cyclementioning
confidence: 77%
“…A second group also investigated the effect of the nucleus to cytoplasm ratio on the rate of DNA replication in Xenopus egg extracts (Murphy and Michael, 2013). By titrating sperm chromatin, they found that there is an increase in the time required to replicate sperm nuclei at high nucleus to cytoplasm ratios and, consistent with the work of Collart et al (2013), that this is caused by a decrease in replication origin activation.…”
Section: Mechanisms Regulating Changes To the Cell Cyclementioning
confidence: 77%
“…The proposed model is that maternally-derived MBT inhibitors are present in a fixed volume of embryonic cytoplasm, and once a critical genomic DNA amount is reached, titration of these factors by DNA induces the MBT [1, 14]. Recently, a number of potential limiting components have been identified relevant to the Xenopus MBT [34, 37, 38]. Importantly, none of these factors appear to fully account for the abrupt changes in gene expression and cell behavior that occur at the MBT, and it seems likely that redundant mechanisms regulate this critical developmental transition [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Early MBT induction by microinjection of plasmid DNA into embryos [14] might also have been mediated through the N/C volume ratio as this injected DNA was subsequently shown to assemble into nuclei [46, 47]. Another possibility is that nuclear volume is relevant to models of MBT timing that invoke titration of an inhibitor by DNA binding, and a notable property of the putative limiting components identified to date is that they all act within the nucleus [34, 37, 38]. Perhaps the MBT is regulated not only by the absolute amounts of key DNA-binding factors that are maternally-derived and titrated by DNA to trigger the MBT, but by their nuclear concentrations, determined by changes in total embryonic nuclear volume during development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects on zygotic transcription were moderate (Collart et al, 2013), consistent with the likely existence of multiple titrated molecules, with some having greater influence on replication and others—such as histones—perhaps having greater influence on transcription (Amodeo et al, 2015; Joseph et al, 2017). In addition to histones and replication factors, other candidate titrated molecules include the phosphatase PP2A-B55 (Murphy and Michael, 2013), maternal histone variants (Yue et al, 2013), the DNA methyl transferase xDnmt1 (Dunican et al, 2008), and dNTPs (Landström et al, 1975; Vastag et al, 2011). …”
Section: Nuclear-to-cytoplasmic Ratio Mechanismsmentioning
confidence: 99%